Capital Deepening and Regional Inequality: An Empirical Analysis - Michael Beenstock; Daniyel Felzenshtain; Nadav Benzeev (European Regional Science Association (ERSA), 2010)
We present a simple reproducible methodology for constructing regional capital stock data, which we apply to Israel. We find that capital deepening has been sigma-convergent since 1985. This process is "inverted" since capital stocks and capital-labor ratios in the richer center have been catching-up with their counterparts in the poorer periphery. We explain this phenomenon in terms of fundamental changes in regional policy. Despite this, regional wages have not been sigma-convergent because other wage determinants have been sigma-divergent
Keywords: 330; capital-labor ratios; regional inequalities; regional capital stock; wage convergence; regional human capital stock